The H3-H4 N-Terminal Tail Domains Are the Primary Mediators of Transcription Factor IIIA Access to 5S DNA within a Nucleosome - Vitolo, Joseph M. (American Society for Microbiology, 2000)
Reconstitution of a DNA fragment containing a Xenopus borealis somatic type 5S rRNA gene into a nucleosome greatly restricts the binding of transcription factor IIIA (TFIIIA) to its cognate DNA sequence within the internal promoter of the gene. Removal of all core histone tail domains by limited trypsin proteolysis or acetylation of the core histone tails significantly relieves this inhibition and allows TFIIIA to exhibit high-affinity binding to nucleosomal DNA. Since only a single tail or a subset of tails may be primarily responsible for this effect, we determined whether removal of the individual tail domains of the H2A-H2B dimer or the H3-H4 tetramer affects TFIIIA binding to its cognate DNA site within the 5S nucleosome in vitro. The results show that the tail domains of H3 and H4, but not those of H2A and/or H2B, directly modulate the ability of TFIIIA to bind nucleosomal DNA. In vitro transcription assays carried out with nucleosomal templates lacking individual tail domains show that transcription efficiency parallels the binding of TFIIIA. In addition, we show that the stoichiometry of core histones within the 5S DNA-core histone-TFIIIA triple complex is not changed upon TFIIIA association. Thus, TFIIIA binding occurs by displacement of H2A-H2B–DNA contacts but without complete loss of the dimer from the nucleoprotein complex. These data, coupled with previous reports (M. Vettese-Dadey, P. A. Grant, T. R. Hebbes, C. Crane-Robinson, C. D. Allis, and J. L. Workman, EMBO J. 15:2508–2518, 1996; L. Howe, T. A. Ranalli, C. D. Allis, and J. Ausio, J. Biol. Chem. 273:20693–20696, 1998), suggest that the H3/H4 tails are the primary arbiters of transcription factor access to intranucleosomal DNA.